The Role of Chemical Modifications in the Genome of Negative-Sense RNA Viruses on the Innate Immune Response - María-Alejandra Ceballos; Mónica L. Acevedo (Viruses)
Negative-sense RNA viruses comprise a wide array of viral families, such as Orthomyxoviridae, Paramyxoviridae, Rhabdoviridae, and Morbillivirus, all of which are adept at inciting significant epidemic outbreaks. Throughout their replication cycle, these viruses engage in a variety of RNA modifications, during both the co-transcriptional and post-transcriptional phases, which are mediated by specific enzymatic activities. These chemical alterations play a critical role in shaping viral fitness, particularly in terms of evading innate immune responses. Key chemical modifications, such as adenosine methylation, 2′-O methylation of nucleosides, and adenosine-to-inosine editing, play critical roles in determining the stability, translational efficiency, and immune recognition of viral RNA. These modifications can reduce the activation of immune sensors, thereby suppressing interferon production and broader antiviral responses. In contrast, certain modifications may enhance immune recognition, which opens avenues for novel vaccine and antiviral strategy development. A comprehensive understanding of these RNA chemical modifications and their implications for virus–host interactions is essential for advancing therapeutic strategies aimed at manipulating innate immunity and optimizing the efficacy of RNA-based vaccines. This review examines the mechanisms and implications of RNA chemical modifications in negative-sense RNA viruses, emphasizing their dual roles in either evading or activating the innate immune system.